Analyzing the Influence of using Blooket Application on 7th Grade Students’ Vocabulary Mastery - Dewi, Chiki Pramu; Dwinalida, Kharirunnisa (UM Purwokerto Press, 2025)
This study aims to analyze the influence of using Blooket on vocabulary mastery of seventh grade students of SMP N 3 Kebasen Banyumas. The population data in this study is grade 7 junior high school with a total of 154 students. There are 2 classes for data collection, namely class 7A as an experimental class and 7B as a control class, where the total number of students in both classes is 64 students. which were assigned as an experimental class utilizing Blooket and a control class employing conventional methods. The conventional method is a traditional teacher-centered learning method, where students are passive and the teacher conveys material verbally through lectures without much interaction or creative activity of students. Data were collected through pre-test and post-test and analyzed using IBM SPSS Version 25 for Windows to determine the influence of Blooket in improving vocabulary acquisition. The mean score of the experimental class pre-test was 51.75, which increased to 68.25 in the post-test. Meanwhile, the mean score of the control class increased from 49.56 to 61.25.